Frontier History and Gender Norms in the United States - Samuel Bazzi; Abel Brodeur; Martin Fiszbein; Joanne Haddad (CESifo GmbH, 2024)
This paper explores how historical gender roles become entrenched as norms over the long run. In the historical United States, gender roles on the frontier looked starkly different from those in settled areas. Male-biased sex ratios led to higher marriage rates for women and lower for men. Land abundance favored higher fertility. The demands of childcare, compounded with isolation from extended family, markets, and social infrastructure, constrained female opportunities outside the home. Frontier women were less likely to report "gainful employment," but among those who did, relatively more had high-status occupations. Together, these findings integrate contrasting narratives about frontier women—some emphasizing their entrepreneurial independence, others their prevailing domesticity. The distinctive frontier gender roles, in turn, shaped norms over the long run. Counties with greater historical frontier exposure exhibit lower female labor force participation through the 21st century. Time use data suggests this does not come with additional leisure but rather with more household work. These gender inequalities are accompanied by weaker political participation among women. While the historical frontier may have been empowering for some women, its predominant domesticity reinforced inegalitarian gender norms over the long run.
Keywords: J12; J13; J22; N31; N91; O15; P16; 330; American frontier; culture; fertility; gender norms; labor supply; marriage